MORAL AND ETHICAL VIEWS OF MAHMUD AL-ZAMAKHSHARI - Rahmedova Manzura (International Scientific and Current Research Conferences, 2023)
This article examines the philosophical, moral and ethical views of Mahmud al-Zamakhshari, as well as their content and significance for the process of forming the moral consciousness and worldview of the younger generation.